2021
DOI: 10.1002/advs.202103408
|View full text |Cite
|
Sign up to set email alerts
|

Defective Ultrathin ZnIn2S4 for Photoreductive Deuteration of Carbonyls Using D2O as the Deuterium Source

Abstract: Deuterium (D) labeling is of great value in organic synthesis, pharmaceutical industry, and materials science. However, the state‐of‐the‐art deuteration methods generally require noble metal catalysts, expensive deuterium sources, or harsh reaction conditions. Herein, noble metal‐free and ultrathin ZnIn2S4 (ZIS) is reported as an effective photocatalyst for visible light‐driven reductive deuteration of carbonyls to produce deuterated alcohols using heavy water (D2O) as the sole deuterium source. Defective two‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…For instance, defective ultrathin ZnIn 2 S 4 displays omnipotent reductive deuteration ability for all kinds of unsaturated bonds, including CC, CO and CN. 14 A polymeric semiconductor PCN enables deuteron-methylation of amines with CD 3 OD, 49 and photodecarboxylase Cv FAP mutants realize the kinetic resolution of racemic acids and afford chiral deuterated products. 31 These achievements are still challenging in the organic catalytic field, but it is believed that interdisciplinary collaboration will lead to more possibilities for exploring new radical deuteration methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, defective ultrathin ZnIn 2 S 4 displays omnipotent reductive deuteration ability for all kinds of unsaturated bonds, including CC, CO and CN. 14 A polymeric semiconductor PCN enables deuteron-methylation of amines with CD 3 OD, 49 and photodecarboxylase Cv FAP mutants realize the kinetic resolution of racemic acids and afford chiral deuterated products. 31 These achievements are still challenging in the organic catalytic field, but it is believed that interdisciplinary collaboration will lead to more possibilities for exploring new radical deuteration methods.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Sun and co-workers 14 the protic sacrificial reagent. A range of deuterium-labelled alcohols were obtained in good yields and D-incorporation (Scheme 10).…”
Section: Jin Xiementioning
confidence: 99%
See 1 more Smart Citation
“…Shortly incorporation) under visible-light irradiation using CdSe quantum dots as the photocatalyst (Scheme 6a). 57 59 These strategies provided promising insights into the sustainable and eco-friendly organic synthesis of value-added deuterated chemicals. In addition, all of the above deuteration studies have also attempted deuteration synthesis of pharmaceutical intermediates (Figure 5), pointing to the potential of the PWDTH technique for the pharmaceutical industry.…”
Section: Mechanism Investigationmentioning
confidence: 99%
“…Zhao et al realized the synthesis of deuterium-labeled alkenes with distinguished levels of D incorporation (99%) over nickel nanoparticles supported on carbon nitride (Ni/C 3 N 4 ) (Scheme b) . Also, Sun et al reported a metal-free defective ultrathin ZnIn 2 S 4 nanosheet (D-ZIS) catalyst for photocatalytic deuteration of carbonyls utilizing the in situ generated D protons from D 2 O splitting with decent deuteration incorporation ratios (Scheme c) . These strategies provided promising insights into the sustainable and eco-friendly organic synthesis of value-added deuterated chemicals.…”
Section: Fundamentals Of Photocatalytic Water-donating Transfer Hydro...mentioning
confidence: 99%